2018
DOI: 10.1029/2018sw001884
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Aspects of the Climate of Space Weather Over the Last Five Solar Cycles

Abstract: Each solar maximum interval has a different duration and peak activity level, which is reflected in the behavior of key physical variables that characterize solar and solar wind driving and magnetospheric response. The variation in the statistical distributions of the F10.7 index of solar coronal radio emissions, the dynamic pressure P Dyn and effective convection electric field E y in the solar wind observed in situ upstream of Earth, the ring current index D ST , and the high-latitude auroral activity index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
4
17
0
Order By: Relevance
“…In all these examples, although the extreme superstorm events have a large effect, they are rare and a much larger number of smaller events, described by the core distribution, can also have a significant integrated effect. Lastly, we note that Chapman et al () have recently studied the extreme event tails in several terrestrial disturbance indices during recent maxima of the solar cycle and fitted generalized Pareto distributions. They found that if the mean and variance of the large‐to‐extreme observations can be predicted for a given solar maximum, then a relationship between the core distribution and the extreme tail can be found giving a description of the full distribution.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In all these examples, although the extreme superstorm events have a large effect, they are rare and a much larger number of smaller events, described by the core distribution, can also have a significant integrated effect. Lastly, we note that Chapman et al () have recently studied the extreme event tails in several terrestrial disturbance indices during recent maxima of the solar cycle and fitted generalized Pareto distributions. They found that if the mean and variance of the large‐to‐extreme observations can be predicted for a given solar maximum, then a relationship between the core distribution and the extreme tail can be found giving a description of the full distribution.…”
Section: Introductionmentioning
confidence: 95%
“…The second theorem in extreme value theory is the Pickands‐Balkema‐de Haan theorem and states that the threshold excesses have an approximate distribution within the generalized Pareto distribution family. EVS has been applied to geomagnetic indices (e.g., Chapman et al, ; Mourenas et al, ; Siscoe, ; Silbergleit, , ; Tsubouchi & Omura, ), to the occurrence of very large geomagnetically induced currents (GICs, Lotz & Danskin, ; Thomson et al, ), and to the fluxes of energetic magnetospheric particles (Koons, ; O'Brien et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the distributions of geomagnetic indices. We present results for periods of solar maximum selected using the definition in Chapman et al (); the solar cycle maximum is 3.5 years in duration and begins 2.5 years after the previous minimum. The dates of the solar minima used for the last four solar cycles are determined from the smoothed Monthly International Sunspot Number provided by SILSO World Data Center (); they are the first of the following months: March 1976, September 1986, May 1996, and December 2008.…”
Section: Indices and Their Solar Cycle Variationmentioning
confidence: 99%
“…Extreme value theory and risk analysis have been applied to D ST in order to predict the likelihood of extreme geomagnetic activity (Acero et al, ; Riley, ; Silrergleit, ; Tsubouchi & Omura, ). Both AE and D ST are regularly considered as benchmarks for the specification of the overall magnetosphere‐ionosphere system as they capture overall activity (Chapman et al, ; Lockwood, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both solar wind driving (Tindale & Chapman, 2016 and geomagnetic activity (Chapman et al, 2018;Hush et al, 2015; track the differences in the level of activity at different phases of distinct solar cycles and between cycles of different intensity.…”
Section: 1029/2019gl086524mentioning
confidence: 99%